A general practice intervention for people at risk of poor health outcomes: the Flinders QUEST cluster randomised controlled trial and economic evaluation. Issue 9 (6th April 2022) - Reed, Richard L; Roeger, Leigh; Kwok, Yuen H; Kaambwa, Billingsley; Allison, Stephen; Osborne, Richard H
Abstract: Objective: To determine whether a multicomponent general practice intervention cost‐effectively improves health outcomes and reduces health service use for patients at high risk of poor health outcomes. Design, setting: Clustered randomised controlled trial in general practices in metropolitan Adelaide. Participants: Three age‐based groups of patients identified by their general practitioners as being at high risk of poor health outcomes: children and young people (under 18 years), adults (18–64 years) with two or more chronic diseases, and older people (65 years or more). Intervention: Enrolment of patients with a preferred GP, longer general practice appointments, and general practice follow‐up within seven days of emergency department and hospital care episodes. Intervention practices received payment of 1000 per enrolled participant. Main outcome measures: Primary outcome: change in self‐rated health between baseline and 12‐month follow‐up for control (usual care) and intervention groups. Secondary outcomes: numbers of emergency department presentations and hospital admissions, Medicare specialist claims and Pharmaceutical Benefits Scheme (PBS) items supplied, Health Literacy Questionnaire scores, and cost‐effectiveness of the intervention (based on the number of quality‐adjusted life‐years [QALYs] gained over 12 months, derived from EQ‐5D‐5L utility scores for the two adult groups). Results: Twenty practices with a total of 92 GPs were recruited, and 1044 eligible patients participated. The intervention did not improve self‐rated health (coefficient, –0.29; 95% CI, –2.32 to 1.73), nor did it have significant effects on the numbers of emergency department presentations (incidence rate ratio [IRR], 0.90; 95% CI, 0.69–1.17), hospital admissions (IRR, 0.90; 95% CI, 0.66–1.22), Medicare specialist claims (IRR, 1.00; 95% CI, 0.91–1.09), or PBS items supplied (IRR, 0.99; 95% CI, 0.96–1.03), nor on Health Literacy Questionnaire scores. The intervention was effective in terms of QALYs gained ( v usual care: difference, 0.032 QALYs; 95% CI, 0.001–0.063), but the incremental cost‐effectiveness ratio was 69 585 (95% CI, 22 968–116 201) per QALY gained, beyond the willingness‐to‐pay threshold. Conclusions: Our multicomponent intervention did not improve self‐rated health, health service use, or health literacy. It achieved greater improvement in quality of life than usual care, but not cost‐effectively. Trial registration: Australian New Zealand Clinical Trials Registry, ACTRN12617001589370 (prospective).